CULTIVATING CRITICAL INFERENCE SKILLS: A PROBLEM-BASED LEARNING MODEL FOR HIGH SCHOOL STUDENTS - Sumartono; Sri Wuli Fitriati; Sri Wahyuni; Zulfa Sakhiyya (Indonesian EFL Journal, 2025)
In the era of Industry 4.0, the demand for 21st-century competencies such as critical and inferential reasoning has become increasingly essential for educational success and workplace readiness. However, many traditional classroom practices still focus primarily on content delivery rather than developing students’ higher-order thinking skills. Responding to this gap, this study investigates the effect of the Problem-Based Learning (PBL) approach on enhancing students’ inference skills compared with conventional teaching methods. The research was conducted among in-service vocational English teachers participating in the Teacher Professional Education Program. A quasi-experimental design was employed, involving control and experimental groups, with data collected through pre-test and post-test assessments. The Shapiro–Wilk test confirmed that the data in both groups were normally distributed at both the pre-test and post-test. The findings revealed that the PBL group demonstrated a significant improvement in inference skills, while the control group showed only marginal progress. This indicates that PBL’s student-centered and inquiry-based framework effectively stimulates reasoning processes through problem identification, hypothesis formulation, evidence-based analysis, and reflective thinking. The authenticity of learning contexts in PBL also fosters deeper cognitive engagement and facilitates the transfer of inference skills to novel situations. Consequently, this study provides empirical support for the implementation of constructivist pedagogies in English language teaching, emphasizing the importance of integrating reasoning-oriented learning strategies to develop learners’ critical and inferential thinking. The implications highlight the need for teacher education programs to systematically incorporate PBL in order to cultivate essential higher-order thinking competencies required in the 21st-century professional landscape.